Respostas

2014-06-20T18:59:27-03:00
A)

     - 1  + (-1)              - 1  - 1             -2 - 1                -3         na DIVISÃO de fração
               ----                    ----           ----------             -----       conserva o 1º e inverte o
                2                        2                 2                     2
--------------------- =  --------------- =  -----------    =     ---------     2º multiplicando
            √3                        √3                √3                   √3
          -----                       ------             -----                 -----      
            2                           2                   2                      2


-3        2         -3x2           6              6√3          6√3         6√3      6√3         6√3:6        √3
---- x  ----=  ---------- =  - --------  = -  ----- = - ------- =   - ------ = - ------ = - --------- = - -----
  2      √3          2√3          2√3          2√3√3        2√3²        2.3        6           6:6           1

Resposta = - √3


b)
0 - (-1)            +1
     ----             ------
       2                2              1       2        1x2             2
-----------  =  ---------  =  ------x ------ = ------ =    -------
    2
√3             2√3           2      2√3    2x2√3       4√3
   ------            ------
     2                   2


  2(
√3)        2√3         2√3       2√3         2√3          2√3 :2       √3
-------- =  ---------  =   -------  =  -----  =    ------- =    -----  =   ------
4
√3√3)     4√3.3.        4√3²       4.3           12           12 :2       6